The Integrity of Woman in Novel Between A Wolf and A Dog (2016) by Georgia Blain - Karlina, Gita; Anwar, Desvalini (Universitas Negeri Padang, 2021)
This thesis is an analysis of the Novel Between A Wolf And A Dog (2016) by Georgia Blain. The purpose of this analysis is to find out to which setting and conflict (plot) reveal the efforts of the main female character in the Novel Between A Wolf And A Dog in dealing with problems that come to her and trying to be responsible in doing work as a family therapist. This analysis is related to the concept of feminist agency by Jennifer Leigh Disney. The result of this analysis shows that the main female character has integrity as shown through her circumspection and consistency.